Implementation Of Restorative Justice As A Justice Law Enforcement In Indonesia - Supriyanto, Agus; Santiago, Faisal; Barthos, Megawati (CV. Publikasi Indonesia, 2023)
The law enforcement framework will in general save essential standards as far as satisfying equity, exclusively because of reasons of satisfying legitimate sureness. Victims in a crime, in the National Legal System, the position is not profitable. Because the victim, in the (Criminal) Judicial System, is only an accessory, not the main actor or just a witness. The type of research used by the author in compiling this research is normative legal research or library law research. It should be emphasized that restorative justice is fundamentally a concept, both about justice and due process, not a theory. Because it is the basis for the development of the judiciary, restorative justice is referred to as the philosophy of justice. So, it is possible to view restorative justice as a collection of legal procedures that primarily seek to repair (recover) the losses suffered by crime victims. In the science of criminal law, justice must try to restore the situation to how it was before the crime was committed. The situation changes when someone breaks the law. So that's where the role of law is to protect the rights of every victim of crime. Helpful equity additionally accentuates common liberties and the need to perceive the impacts of social unfairness and in basic ways review them, as opposed to just giving the culprits formal or lawful equity and casualties not getting any equity. Supportive equity likewise looks to reestablish casualties' security, individual regard, respect, and all the more significantly, a feeling of control. The helpful equity framework can be applied in the event that the lawful culture in a nation requires its execution for a specific case.